Use of Pentamethyldisiloxane in the Palladium-Catalyzed Cyclization/Hydrosilylation of Functionalized Dienes - Pei, Tao; Widenhoefer, Ross A (Organic letters, 2000)
Pentamethyldisiloxane reacts with a range of functionalized dienes in the presence of a catalytic 1:1 mixture of (N−N)Pd(Me)Cl [N−N = 1,10-phenanthroline or (R)-(+)-4-isopropyl-2-(2-pyridinyl)-2-oxazoline] and NaBAr4 [Ar = 3,5-C6H3(CF3)2] to form the corresponding silylated carbocycles in good yield and with good stereoselectivity. Treatment of these silylated carbocycles with excess KF and peracetic acid at room temperature for 48 h formed the corresponding alcohols in excellent yield with retention of stereochemistry.